[Omicron] (αsαt) (non)decoupling effects within the top-sector of the MSSM - Mihaila, Luminita; Zerf, Nikolai (Journal of high energy physics, 2017)
In this paper we compute the O(αsαt)O(αsαt) \mathcal{O}\left(α_sα_t\right) threshold corrections to the running strong coupling constant, the top-Yukawa coupling and the top-quark mass within the MSSM. These parameters present a non-decoupling behaviour with the supersymmetry scale MSUSY . Our numerical analysis shows that the mixed QCD-Yukawa corrections can amount to few GeV for the running top-quark mass and range at the percent level for the top-Yukawa coupling.
Im Titel ist [omicron] als griechischer Buchstabe dargestellt, "s" und "t" sind tiefgestellt
Gesehen am 28.11.2017